Desnutrición escolar - Muñoz Arias, Myriam Pamela (2017)
Malnutrition is the condition that develops when the body does not get the right amount of the vitamins, minerals, and other nutrients it needs to maintain healthy tissues and organ function. This deficiency is believed to start in the womb of the mother which can later cause delays in the learning process. The primary objective of this survey is to analyze strategies that will help to improve the feeding of children so that they may be able to obtain an excellent academic performance, as well as an outgoing profile of the students framed in Sumak Kawsay. The right nutrition for children will improve the quality of the learning process of students. In order to carry out the project, we will use research methods which include: Inductive, deductive, analytical, and qualitative-quantitative....